2019
DOI: 10.23887/jppsi.v2i2.19384
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Strategi Belajar Kognitif, Metakognitif Dan Sosial Afektif Terhadap Hasil Belajar Ipa

Abstract: Penelitian ini bertujuan menganalisis pengaruh strategi belajar kognitif, metakognitif dan sosial afektif terhadap hasil belajar IPA. Jenis penelitian adalah ex post facto yang bersifat korelasional. Populasi penelitian adalah seluruh siswa kelas VIII SMP Negeri se-Kecamatan Tegallalang Tahun Pelajaran 2018/2019 yang berjumlah 943 siswa. Sampel penelitian berjumlah 273 siswa yang diambil dengan teknik proporsional random sampling. Data hasil belajar IPA dikumpulkan menggunakan metode tes dan data strategi bela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 1 publication
0
7
0
9
Order By: Relevance
“…The study reported that skilled second lan-guage readers are students with high reading comprehension scores or high second language knowledge. They differ from less proficient second language readers in using the strategy (Osuji, 2017;Fauziah, 2017;Sri Widyantari, Nyoman & Pande Latria, 2019;Ruhina, 2020).…”
Section: Research Problemmentioning
confidence: 99%
“…The study reported that skilled second lan-guage readers are students with high reading comprehension scores or high second language knowledge. They differ from less proficient second language readers in using the strategy (Osuji, 2017;Fauziah, 2017;Sri Widyantari, Nyoman & Pande Latria, 2019;Ruhina, 2020).…”
Section: Research Problemmentioning
confidence: 99%
“…It can be concluded that the note-taking strategy aims to facilitate the student learning process. It is supported by previous research, which states that student learning strategies that make students feel comfortable will make students happier in learning (Firmansyah, 2013;Suhendro, 2020;Widyantari et al, 2019). Other research also states that students who are highly willing to learn will certainly affect student learning outcomes (Raharja et al, 2019;Rahmayani & Amalia, 2020).…”
Section: Discussionmentioning
confidence: 71%
“…Strategi belajar ialah upaya yang dilakukan seseorang ketika belajar untuk dapat memahami, menggunakan dan mengolah informasi yang ia dapatkan secara individu (Widyantari et al, 2019). Strategi belajar yang biasanya dilakukan oleh mahasiswa ialah dengan memperiapkan…”
Section: Strategi Belajarunclassified